Exploring the role of language policy in facilitating multilingual communication among pesantren students - Sa'adah, Alfiyatus; Rohmah, Zuliati; Junining, Esti; Abdullah, Hazlina (Universitas Muhammadiyah Sidoarjo, 2025)
This study investigates the daily life of a student navigating a multilingual language policy at Pesantren Progresif Bumi Sholawat, an Islamic boarding school in East Java. It aims to explore how the use of multiple languages, primarily English, supported by Japanese, Arabic, and Javanese, shapes the student’s communication, identity formation, and emotional adaptation. Utilizing a qualitative methodology with a narrative inquiry approach, the study draws on Vygotsky's sociocultural theory, which emphasizes social interaction and cultural tools as the foundation of language acquisition. Data were collected through in-depth interviews and analyzed using thematic narrative analysis. The findings show three key aspects, First, students experience both cognitive and emotional tension while adapting to the English-only policy. Second, support from peers and teachers serves as crucial scaffolding that helps them build confidence and overcame language anxiety. Third, students gradually form a hybrid identity that integrates Pesantren values with global communication competence This research contributes to the field of language policy by foregrounding student voices, affective experiences, and practical directions for enhancing multilingual practices in Islamic boarding schools.